샐러리 종자 에탄올 추출물의 산화방지 활성 및 수중유적형 유화계에서의 산화안정성 - 김민아(Min-Ah Kim); 한창희(Chang Hee Han); 이재철(Jae-Cheol Lee); 김미자(Mi-Ja Kim) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2017)
This study was conducted to examine the antioxidant activity of 80% ethanol extract of celery seeds and to verify the effectiveness of extracts as a natural antioxidant to improve the stability of oil-in-water emulsions. The radical scavenging activity of 80% ethanol extract of celery seeds was significantly increased at 0.125, 0.25, and 0.5 mg/mL (p<0.05). Additionally, the total phenolic content and FRAP value were equal to 8.2±2.3 mol tannic acid equivalent/g extract and 195.0±12.6 mol ascorbic acid equivalent/g extract, respectively. The headspace oxygen content was significantly higher in the group treated with 80% ethanol extract of celery seeds than in the control group (p<0.05). The amounts of lipid hydroperoxide and conjugated diene were significantly reduced compared to the control group (p<0.05). The results showed that the extract of celery seeds had excellent antioxidant ability and it could be used as a natural antioxidant owing to the increased oxidative stability of the emulsified product.